2016
DOI: 10.1038/nrgastro.2016.96
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic mucosal resection and endoscopic submucosal dissection of large colonic polyps

Abstract: Almost all large and complex colorectal polyps can now be resected endoscopically. Piecemeal endoscopic mucosal resection (PEMR) is an established technique with fairly low complication risk and good short-term and medium-term outcomes. Several modifications to the basic injection and snare technique have been developed contributing to safer and more complete resections. Delayed bleeding requiring reintervention is the most troublesome complication in 2-7% of patients, particularly in those with comorbidities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 143 publications
(153 reference statements)
1
48
0
Order By: Relevance
“…Two studies from Japan have shown that ESD is associated with a low recurrence rate after removal of malignant non-pedunculated lesions in the colon (0 %) and rectum (6 %) with low-risk criteria 5 12 . ESD is a technically difficult procedure and despite an increase in reports from the West, dissemination of ESD outside Asia has been slow 28 29 30 31 32 . At present the role of ESD in western countries is under investigation and the specific role of ESD for treatment of malignant non-pedunculated colorectal lesions is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies from Japan have shown that ESD is associated with a low recurrence rate after removal of malignant non-pedunculated lesions in the colon (0 %) and rectum (6 %) with low-risk criteria 5 12 . ESD is a technically difficult procedure and despite an increase in reports from the West, dissemination of ESD outside Asia has been slow 28 29 30 31 32 . At present the role of ESD in western countries is under investigation and the specific role of ESD for treatment of malignant non-pedunculated colorectal lesions is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Additional validation of topics that may already be considered as having sufficient evidence were noted, such as a comparison of long-term outcomes of gastric ESD with surgery for EGCs that fulfilled the expanded indication, 40 or therapeutic outcomes of ESD of differentiated EGCs 41 or colorectal tumors 42 in Western countries. Studies that compared EMR with ESD for the treatment of superficial colorectal neoplasia [43][44][45] received attention from various audiences. Studies about the development and validation of novel ESD techniques, such as endoscopic mucosa-sparing lateral dissection for the treatment of gastric subepithelial tumours or ESD for subepithelial tumours of the colon and rectum also received attention.…”
Section: 39mentioning
confidence: 99%
“…Complex colorectal polyps defined as those greater than 2 cm or those positioned in difficult anatomic locations can be a major challenge for endoscopic therapy 1 2 3 . Underwater endoscopic submucosal dissection (UESD) has recently emerged as a potential technical solution to facilitate complex polyp removal 4 .…”
Section: Introductionmentioning
confidence: 99%